Methodological strategy that should be used in class by the teacher to develop the writing skill. - González Granda, Priscilla Lizbeth (Machala : Universidad Técnica de Machala, 2015)
The present investigation has as an objective to determine a methodological strategy that should be use in class to develop writing skills in the teaching learning process of English. In the statement of the problem it refers to the limited development of writing skills of English language, which prevents there is a real interaction between teacher- student, causing a deficiency at the time of writing different texts notoriously affecting the student , because it ignores the grammatical rules of writing the second language. Therefore in the development of this research a methodological strategy is presented to be used in class by the teacher while writing occurs. In a detailed way the process of writing is displayed, and the purpose of the teacher in the process of writing, it references to the techniques and activities used in class to efficiently develop the skill of writing in a second language. One of the methods used during the development of this research was the analytical - critical method because it allowed us to analyze the history of the phenomenon, the nature of the problem, the object of study, and also allowed to argue the solution.
La presente investigación tiene como objetivo determinar una estrategia metodológica que debe ser su uso en clase para desarrollar habilidades de escritura en el proceso de enseñanza aprendizaje de Inglés. En el planteamiento del problema se refiere al escaso desarrollo de las habilidades de escritura de la lengua Inglés, que impide que existe una verdadera interacción entre profesor-estudiante, causando una deficiencia en el momento de escribir diferentes textos que afecta notoriamente el estudiante, porque ignora la reglas gramaticales de la escritura de la segunda lengua. Por lo tanto, en el desarrollo de esta investigación se presenta una estrategia metodológica para ser utilizado en clase por el profesor mientras se produce la escritura. De una manera detallada se muestra el proceso de la escritura, y el propósito del profesor en el proceso de la escritura, que hace referencia a las técnicas y actividades utilizados en clase para desarrollar eficazmente la habilidad de escribir en un segundo idioma. Uno de los métodos utilizados durante el desarrollo de esta investigación fue el analítico - método crítico porque nos permitió analizar la historia del fenómeno, la naturaleza del problema, el objeto de estudio, y también permitió a discutir la solución.
Keywords: METHODOLOGICAL STRATEGY; WRITING SKILL; CLASS; TEACHER